Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Pada Mobil Honda HR-V Di Kota Semarang - Riska Amalia (Universitas Diponegoro, 2016)
The development of the automotive industry in Indonesia make the level of competition becomes tight, especially in the automobile industry. The car manufacturers continue to push the product. It is evident from the diverse array of brands and types of cars in Indonesia. This study aimed to analyze the factors that influence consumer purchase decisions in the purchase of cars Honda HR-V in Semarang. The primary data used by giving questionnaires to consumers Honda HR-V with a total of 97 respondents are determined using a formula table Slovin. Respondents were taken by using purposive sampling method.The research findings indicate the factor analysis test, which qualifies Measure of Sampling Adequacy (MSA) to be above 0.5, the Product Quality variable (0.693), Variable Brand Awarness (0.766), Variable Brand Image (0,687), and Variable Lifestyle (0.611). From the analysis that the four variables have a significant influence on purchasing decisions.The conclusion and recommendation of product quality, brand awareness, brand image and lifestyle significantly influence purchasing decisions either partially or simultaneously. Suggested to the producers that assemble cars Honda can provide better products. It also might influence the purchase decisions of consumers.